Chronic diseases in the context of fundamental biology - Kordium, V.A. (Вiopolymers and Cell, 2017)
The problem of chronic diseases is analyzed from the perspective of general biology. We develop and substantiate the idea that the chronic diseases are an evolutionary mechanism of cleansing the population and the species of its mutational load. This is achieved by keeping self-restoration systems of a chronically damaged organism in the off-state, unlike in the ‘permissible’ self-restoration triggered by the acute damage. Evolutionary, chronic diseases serve as a somatic marker for the accelerated elimination of their carriers. З позицій уявлень загальної біології, аналізується проблема хронічних хвороб ( «хроніки»). В рамках такого аналізу формується і обгрунтовується уявлення про те, що хроніка є еволюційно вироблений механізм очищення популяції, виду від мутаційного вантажу. Це досягається виключенням систем самовідновлення в організмі, який довго не відновлюється при впливі на нього природних факторів. Відповідно хроніка в природних умовах перетворюється на маркер прискореної елімінації її носія. С позиций представлений общей биологии, анализируется проблема хронических болезней («хроники»). В рамках такого анализа формируется и обосновывается представление о том, что хроника представляет собой эволюционно выработанный механизм очистки популяции, вида от мутационного груза. Это достигается выключением систем самовосстановления в организме, который долго не восстанавливается при воздействии на него природных повреждающих факторов. Соответственно хроника в природных условиях превращается в маркер ускоренной элиминации её носителя.